2011
DOI: 10.1021/ac1031012
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Robust Method for Determining the Number of Basic Sites in Peptides and Proteins Using Electrospray Ionization Mass Spectrometry

Abstract: A solution additive has been discovered that can be used to measure the number of basic sites in a peptide or protein using electrospray ionization (ESI) mass spectrometry. Addition of millimolar amounts of perchloric acid (HClO4) to aqueous solutions that contain peptides or proteins results in the noncovalent adduction of HClO4 molecules to the multiply charged ions formed by ESI. For 18 oligopeptides and proteins, ranging in molecular weight from 0.5 to 18.3 kDa, the sum of the number of protons plus maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
28
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 38 publications
10
28
2
Order By: Relevance
“…The sum of the number of acid molecules and protons for the most abundant ion is equal to the 13 basic sites in ubiquitin. This correlation between adduction and the number of basic residues has been reported previously [4850]. …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The sum of the number of acid molecules and protons for the most abundant ion is equal to the 13 basic sites in ubiquitin. This correlation between adduction and the number of basic residues has been reported previously [4850]. …”
Section: Resultssupporting
confidence: 87%
“…Indeed, small cations (specifically Na + and K + ) [38, 39] and anions (SO 4 2− and PO 4 3− ) [40] are typically considered nuisances during the analysis of biological molecules by both ESI and matrix-assisted laser desorption ionization (MALDI)-MS, and many steps have been taken to reduce their presence in the mass spectra of proteins [3941] and nucleic acids [38, 42, 43]. The few MS studies involving the interactions of proteins with small ions have examined more the ion’s effects on overall signal [44, 45], the observed charge state distribution [46, 47], how many ions (or neutral acid molecules of the anion) adduct to the protein [4850], or how to best minimize ion adduction [3941]. With respect to adduction of anions to protein ions, the anions sulfate [40], perchlorate [49, 50], and iodide [48] adduct to proteins, with the extent of adduction of the latter two anions correlating well [49] or exactly [48, 50] with the number of unmodified basic sites (arginine, lysine, histidine, and N-terminus) in the protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that if several sites on the peptide/protein were of comparable basicity, a particular acid could be found that would be able to attach multiple times as a neutral molecule at various basic sites on the peptide/protein. This model is supported by important results from Williams and coworkers [23,24], who added HClO 4 to peptides/proteins in solution in order to determine the number of basic sites in these peptides/proteins. According to our model, the success of this method arises from the advantageous matching of the GB of ClO 4 -with GB app of the typical amino site on a peptide/protein.…”
Section: Positive Ion Modelmentioning
confidence: 55%
“…If indeed, all of the amino sites have apparent GBs that are adequately matched with ClO 4 -, each basic amino group may hold a stable adducted HClO 4 molecule. As recognized by the Williams group [23,24], this allows the calculation of the number of basic sites from an assessment of the maximum number of HClO 4 molecules attached (each one a neutral site) plus the number of protonated sites (equal to the charge state of the protein/peptide). The success of this method hinges upon the ability to either protonate or form a stable HClO 4 adduct at every basic site.…”
Section: Positive Ion Modelmentioning
confidence: 99%